Characterization of Dietary Fiber Extracts from Corn (Zea mays L.) and Cooked Common Bean (Phaseolus vulgaris L.) Flours and Evaluation of Their Inhibitory Potential against Enzymes Associated with Glucose and Lipids Metabolism In Vitro - Amanda B. Serna-Perez; Guadalupe Loarca-Piña; Ivan Luzardo-Ocampo (Biology and Life Sciences Forum, 2021)
This research aimed to characterize dietary fiber (DF)-aqueous extracts from corn (commercial and Northwestern White Population) and common bean (cv. Bayo Madero) flour blends, evaluating their inhibitory effect on enzymes involved in glucose/lipid metabolism in vitro. Insoluble fiber showed the highest content of total phenolics, chlorogenic and ellagic acids being the main identified phenolics. Soluble fiber displayed the α-glucosidase and pancreatic lipase inhibitions (20–25%). The results suggested that corn/bean DF is a functional ingredient to potentially alleviate obesity and type II diabetes.